Potret Tumpuan Perguruan Tinggi dalam Upaya Alih Teknologi: Portrait of University in Technology Transfer Effort - Sulistianingsih, Dewi; Setiawan, Andry; Prabowo, Muchammad Shidqon (Fakultas Hukum Universitas Negeri Semarang, 2021)
Universities in Indonesia are a place for researchers, academics, and devotees to contribute their thoughts, develop science and technology, and develop science and technology to be able to benefit the people of Indonesia. College as a forum for the development of science and technology not only studies and studies science and technology but is also able to apply it in learning and apply it in people's lives. It is a tough task for universities to carry out, but the demands of the era and human civilization make universities must be able to adapt to the existing conditions. Technology transfer is the right target to be carried out by universities, considering that Indonesia is lagging behind in developing technology in the international world. The purpose of technology transfer at the University, one of which is to catch up with Indonesia's current technological advances. This paper is the result of a research conducted using a normative juridical method. The data used is secondary data with a variety of literature, both books, journals, laws and regulations. The results of this study can be seen that universities have made various efforts to improve technology transfer even though there are several obstacles and challenges faced by universities. Nevertheless, higher education remains the center for developing science and technology and increasing technology transfer in order to provide the greatest benefit to the Indonesian state and nation.